Procalcitonin as a diagnostic biomarker of sepsis: A tertiary care centre experience. Issue 3 (May 2019) - Gupta, Shefali; Jaswani, Pradeep; Sharma, Raj K.; Agrawal, Suraksha; Prasad, Narayan; Sahu, Chinmoy; Gupta, Amit; Prasad, Kashi N.
Abstract: Introduction: Despite the advancement in diagnostic modalities of sepsis, it is still a leading cause of morbidity and mortality. Differentiation between sepsis and non-infectious disease states remains a diagnostic challenge. Procalcitonin (PCT) is useful for the diagnosis of sepsis but it varies in cut-off ranges at different clinical settings. The aim of this study was to correlate serum PCT levels with cultures and to evaluate the best cut-off values with high sensitivity and specificity for PCT. Methodology: This prospective study included 305 patients from different medical wards; the patients were classified into group I: controls (n = 46), group II: culture-negative sepsis (n = 76) and group III: culture-positive sepsis (n = 196). Mean p value <0.05 was considered significant. Results: PCT levels were significantly higher in group II and group III as compared with group I. In group II, the best cut-off point for PCT was 1.3 ng/ml with 87.30% sensitivity and 78.26% specificity (area under curve 0.86). In group III, the best cut-off value of 2.20 ng/ml with 98.47% sensitivity and 89.13% specificity was found (AUC 0.96). Conclusion: Procalcitonin can accurately differentiate culture-negative and culture-positive sepsis from non-infectious diseases, thus making it a promising biomarker in diagnosis of bacterial sepsis.